NILAI PENDIDIKAN ISLAM UNTUK ANAK PADA TEKS HIKAYAT WASIAT NABI MUHAMMAD (Sebuah Kajian Filologi Telaah Isi Teks di Perpustakaan Nasional Jakarta) - Diah Ratna W (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2013)
One of the purposes of this research is to preserve texts from physical deterioration. The primary text examined is housed in the Jakarta National Library, while other related texts in microfiche form at the Leiden University Library were not included due to limitations of time and access. In addition to preservation, this research aims to reveal and interpret the messages contained within the texts. Given the fragile condition of the manuscripts, immediate conservation efforts are essential; without such efforts, the texts risk irreversible deterioration in the near future. The loss of these texts would not only diminish national cultural heritage but also erase the moral, religious, and social values embedded within them. Through these texts, a comprehensive understanding of past societal thought patterns, cultural practices, beliefs, and value systems can be obtained. Text A serves as the primary transliterated text and forms the basis for comparison with Text B, as Text A presents a more complete narrative structure and storyline. The values conveyed in this saga reflect the author’s intended moral messages to readers, including prohibitions and guidance related to marital conduct, mutual assistance, compassion for humanity, the obligation of prayer for every Muslim, respect for parents and teachers, and prohibitions against immoral behavior and consuming unlawful food, all of which constitute the core messages. In addition, the text also conveys supporting messages such as the practice of remembrance (dzikir), encouragement to seek and teach knowledge, proper sleeping procedures, the importance of repentance, and the recommendation to begin activities using the right hand.